Introducing a model for how knowledge-driven agile innovation can drive digital transformation in firms - BHATTACHARYA, Lipika (Institutional Knowledge at Singapore Management University, 2022)
Digital transformation often arises from the distribution of tasks among interdisciplinary teams of experts. One important factor that determines the success of digital transformation relates to an organization’s ability to innovate in an agile manner. In this article, we identify key drivers of digital transformation, which include organizational agility, knowledge management and innovation. Another crucial aspect of knowledge management relates to the coordination of knowledge. It is important for organizations to focus on knowledge coordination because the lack of coordination can dissuade them from meeting the demands for flexibility and speed during digital transformation, thereby negating the potential benefits from adopting an agile innovation methodology. To examine these issues, we introduce a model to establish how agile knowledge management practices can foster innovation in an organization’s digital transformation. Our model also highlights how knowledge coordination can create an environment that fosters organizational agility. To facilitate knowledge-driven agile innovation, we further highlight several people management practices that can play a role in fostering knowledge sharing behaviors during digital transformation. In addition, our article illustrates how agile innovation can play a key role in the knowledge management aspect of an organization’s digital transformation using case studies, including that of General & Marine Agents Pte Ltd, an insurance broker headquartered in Singapore.